Faktor yang Berhubungan dengan Rendahnya Pemakaian Alat Kontrasepsi Dalam Rahim (AKDR) - Meirina Namiarta BR Gultom; Siti Aisyah; Satra Yunola (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2023)
World Health Organization (WHO), the uses of contraception is increasing in several parts of world especially in Asia and Latin America, and the lowest is in Sahara Africa. Globally, the uses of modern contraceptives increase non-significantly from 54% in 1990 to 57.4% in 2014. The method used in this study was analytic survey with cross sectional approach. The statistical test was chi-square test. The population of this study was all KB acceptor at Perumnas Public Health Center, Lahat District on January to May 2021 which was estimated to be 1826 respondents and the sample was 95 respondents. The univariate analysis showed that of 95 respondents studied, there was 14 respondents (14,7%) used intrauterine contraceptives, whose with positive behavior was 35 respondents (36,8%), and whose with good knowledge was 44 respondents (46,3%). The result showed that there was significant relationship between husband support and the low use of intrauterine contraceptives p.value 0,028 < ? = 0,05, there was significant relationship between behavior and the low use of intrauterine contraceptives p.value = 0,045 < ? = 0,05, and there was significant relationship between knowledge and the low use of intrauterine contraceptives p.value = 0,020 < ? = 0,05. The results of this study are expected to increase the use of intrauterine contraceptives of KB acceptor.